A sustainable, high-performance process for the economic production of waste-free microbial oils that can replace plant-based equivalents. Issue 9 (27th June 2019) - Masri, Mahmoud A.; Garbe, Daniel; Mehlmer, Norbert; Brück, Thomas B.
Abstract : A economically and ecologically viable, fully integrated yeast oil process. Abstract : Globally, biofuel and oleochemical production based on plant oils negatively affects biodiversity. As an alternative triglyceride source, lipid production from oleaginous yeasts faces numerous challenges in feedstock availability, lipid productivity, downstream processing, and waste treatment, prohibiting the design of a cost-competitive process with regard to plant equivalents. In this study, we present a fully integrated operation for microbial oil production, which consolidates upstream and downstream processing with side-stream recycling. Co-fermentation of sugar and acetic acid was successfully implemented in fed-batch, semi-continuous, and continuous fermentation modes. Process validation was conducted at a 25 L scale with a lipid productivity of 1.2 g L −1 h −1 . Cutaneotrichosporon oleaginosus cell debris was used as an inducer in Trichoderma reesei fermentation for on-site generation of yeast-specific cell-wall hydrolases. In situ hydrolase application allowed for efficient C. oleaginosus cell lysis (85% w/w) and simultaneous lipid release. A subsequent centrifugation step yielded 90% (w/w) recovery of intracellular lipids without the need for any organic solvent. The nutrient-rich water phase was applied as an internal sugar source for subsequent yeast fermentation cycles. With this yeast hydrolysate, the lipid productivity was considerably increased to 2.4 g L −1 h −1 . A techno-economic analysis of the current lipid production processes estimated costs at 1.6 per kg lipid. Moreover, life cycle assessment analysis indicated an emission of 3.56 kg CO2 equivalents for every 1 kg produced yeast oil. Accordingly, we established an integrated operation for bioconversion of acetic acid and sugar to sustainable lipids at maximum productivity coupled with minimal waste generation and energy consumption.